4CPS-251 Evaluation of Clostridium difficile infection management prior to implementation of a protocol for improvement. (14th March 2021) - Acín Garcés, V; Vinuesa Hernando, JM; Gracia Piquer, R; Fresquet Molina, R; Morte Romea, E; Gimeno, M; Seral García, C; Arenere Mendoza, M
Abstract : Background and importance: Clostridium difficile disease (CDD) is the leading cause of infectious diarrhoea in the hospital environment. Aim and objectives: The objective was to evaluate the characteristics of patients with CDD prior to the implementation of a checklist for the diagnosis and treatment of CDD. Material and methods: This was a retrospective observational study of CDD cases in a third level hospital during 2019. Positive cases were evaluated according to the checklist: vulnerability (cancer, neutropenic, transplant, inflammatory bowel disease (IBD) or prolonged antibiotic treatment), severity (according to leucocytosis, renal function or presence of hypotension, shock or ileus), risk of recurrence (according to age, CDD the previous year, positive toxin or persistence of diarrhoea on the fifth day of treatment), treatment and antibiotic intake in the previous 3 months. Results: 126 cases of CDD were identified in 100 patients, with a median age of 76 (1–96), and 59% were women. 19.8% of the cases were vulnerable (5 transplants, 3 IBD, 8 oncological and 1 immunosuppressed). Severity of the episodes was assessed in 116 patients, with 62.9% not serious, 31.9% serious and 5.2% (6) fulminant. The fulminant cases were hypotension/shock (4) and megacolon (2). The risk of recurrence was high in 10.8%, intermediate in 55.0% and low in 34.2%. Of the 100 patients diagnosed, 21% (21) presented with at least one recurrence and 4% (4) with multiple recurrences. In addition, 7% had some episodes in the previous years. Regarding treatment of the 126 episodes of CDD: 20.6% were treated with metronidazole, 58.7% with vancomycin (8.7% followed by vancomycin taper), 7.2% with metronidazole+vancomycin, 3.9% with fidaxomycin, 3.2% with metronidazole+vancomycin+fidaxomycin, 0.8% with metronidazole+fidaxomycin, 0.8% with vancomycin+fidaxomycin and 4.8% were not treated as they were considered to be self-limiting processes. In 82.5%, the patient received at least one antibiotic in the previous 3 months. Conclusion and relevance: Patients with CDD were older (76 years). Despite the low vulnerability of the population, severe and fulminant cases reached almost 40%. Treatment was heterogeneous, but metronidazole and vancomycin remained the standard of care. In 82% of cases, patients had received prior antibiotic treatment, an aspect of particular relevance to the future management of CDD, as 21% of patients presented with recurrence. References and/or acknowledgements: Conflict of interest: No conflict of interest